HIV-1 infection of macrophages differentially primes NK-cell cytotoxicity and proinflammatory cytokine production - Leonore Mensching; Maya Beiersdorfer; Sebastian Schloer; Sandra Köllmann; Friederike Reinsberg; Benedetta Padoan; Pia Fittje; Timo Trenkner; Annika Zaayenga; Gloria Martrus; Maher Almahfoud; Christina M. Stürzel; et al. (iScience)
Summary: Natural killer (NK) cells are innate cytotoxic lymphocytes with antiviral functions explored in “shock and kill” strategies to eliminate the HIV-1 reservoir. For optimal activity against infected targets, NK cells require priming. This study examined how macrophages prime NK cells following HIV-1 infection. We found that HIV-1-infected monocyte-derived macrophages upregulated membrane-bound IL-15Rα, NKG2D ligands, CD48, and IL-18. While crosstalk between NK cells and infected macrophages enhanced proinflammatory cytokine production, it led to only weak priming of NK-cell cytotoxicity. In people living with HIV-1 (PLWH) on antiretroviral therapy, macrophage priming remained intact and polyfunctional, with the strongest response in CD56dim KIR+ and/or NKG2A+ NK cells. However, CD56neg NK cells —a subset unique to HIV-1 infection— remained dysfunctional. These findings elucidate how HIV-1 alters macrophage-NK cell crosstalk and underscore the need for therapeutic strategies that enhance NK-cell cytotoxicity in efforts toward a functional HIV-1 cure.